Digital Transformation of Gayo Coffee MSMEs through Digital Branding: Challenges and Strategies for Enhancing Global Competitiveness - Muhammad Aditia Rizki (Winaya Inspirasi Nusantara Foundation, 2027)
Micro, small, and medium enterprises (MSMEs) engaged in Gayo Arabica coffee production in Aceh, Indonesia, occupy a globally recognized niche protected by Geographical Indication (GI) status, yet many remain marginalized within the global value chain due to uneven digital adoption, limited digital literacy, and fragmented institutional support. This study aims to critically examine the practice of digital transformation among Gayo coffee MSMEs, with particular attention to digital branding, institutional and public-administration support, and the strategic opportunities and barriers shaping their global competitiveness. A library research design was employed, synthesizing peer-reviewed journal articles, conference proceedings, and institutional reports published between 2020 and 2026 and indexed in Scopus, Google Scholar, and SINTA. Thematic and comparative synthesis techniques were applied to extract, categorize, and cross verify findings across sources. The synthesis reveals that digital branding and financial technology adoption substantially strengthen customer engagement and financial performance among Gayo coffee MSMEs; however, these gains remain constrained by low digital literacy, weak cross-stakeholder collaboration, and inconsistent policy implementation at the sub-national level. Collaborative governance arrangements involving government agencies, cooperatives, and digital platforms emerge as a decisive enabler of sustained digital transformation. The findings offer a transferable model for other Geographical Indication based agricultural commodities seeking to convert cultural and ecological distinctiveness into digitally mediated global competitiveness, while also informing public administration strategies aimed at closing the digital divide among smallholder based MSMEs.